Effects and safety of acne vulgaris with external application of herbal medicines: A protocol for systematic review and meta analysis. Issue 26 (2nd July 2021) - Zhou, Jin; Li, Xiaoxiao; Chen, Haimin; Qi, Zirong; Shao, Shujun; Tang, Yinshan; Jiang, Chenglong
Abstract: Background: Acne vulgaris (AV) is a common dermatologic disease. The morbidity is increasing annually. External application of herbal medicines (EAHM) has been pervasively used in the therapy of AV. EAHM, as the traditional Chinese therapy, is widely applied in clinical trials for AV. The aim of this review is to systematically evaluate the efficacy and safety of EAHM in the therapy for AV. Methods: We will conduct an electronic search of 13 databases from their inception to May, 2020, including PubMed, EMBASE, MEDLINE, Web of Science, Cochrane Library, SpringerLink, WHO International Clinical Trials Registry Platform, Wanfang China database, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chinese Scientific Journal Database, as well as China's Conference Papers Database and China Dissertation database. Other valid search strategies will also be retrieved to complete this review. All randomized controlled trials in which EAHM was used for the treatment of AV will be adopted. Two researchers will select eligible studies respectively according to a predefined protocol. Methodological quality will be assessed with Cochrane risk of bias by means of RevMan V.5.3.5 software. Results: This systematic view will present a high-quality synthesis based on current evidence of EAHM intervention for AV patients. Conclusion: The summary of our systematic view will provide evidence to judge whether EAHM is an effective and safe intervention for AV patients.